1977
DOI: 10.1128/aac.11.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Toxicity Associated with 5-Fluorocytosine Therapy

Abstract: Bone marrow toxicity occurred in 4 of 15 patients treated with 5-fluorocytosine (5-FC) for serious fungal infections. The development of marrow toxicity appeared to be related to serum 5-FC levels of 125 ,g/ml or greater. In three patients, accumulation of toxic levels of 5-FC was related to diminished renal function. One patient with acute renal failure and prolonged high levels of 5-FC developed marrow aplasia and died of bacterial sepsis. Three patients experienced leukopenia, which was readily reversed whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(51 citation statements)
references
References 19 publications
2
49
0
Order By: Relevance
“…Use of significantly smaller amounts of drug or dosing to achieve lower peak levels may allow flucytosine administration with much less concern about related toxicities. Several studies have shown that bone marrow toxicities are essentially eliminated when levels in serum remain between 40 and 60 mg/liter (14,18). Even these "safe" levels would not be necessary if the pharmacodynamic predictions provided here are valid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of significantly smaller amounts of drug or dosing to achieve lower peak levels may allow flucytosine administration with much less concern about related toxicities. Several studies have shown that bone marrow toxicities are essentially eliminated when levels in serum remain between 40 and 60 mg/liter (14,18). Even these "safe" levels would not be necessary if the pharmacodynamic predictions provided here are valid.…”
Section: Discussionmentioning
confidence: 99%
“…The currently available therapies result in unacceptably high failure rates (10,30). In addition, the available antifungal therapies often produce significant toxicities (14,18). Although the new antifungal agents appear to be promising, approaches that optimize the efficacies and limit the toxicities of currently available agents through rational pharmacodynamic dosing may offer more immediate impact (15).…”
mentioning
confidence: 99%
“…However, only a limited number of effective agents, e.g., amphotericin B and 5-fluorocytosine, have been available, and various problems have been associated with their usage (5,8,9,12,14,18,22,26). Recently, imidazole compounds have been reported to have antifungal properties (7,13,23, 27), and the clinical efficacy of compounds such as miconazole, miconazole nitrate, and ketoconazole (formerly designated R41,400), is under investigation (10,11,24,25).…”
mentioning
confidence: 99%
“…However, toxicity does develop in patients treated with 5-FC and is seen most commonly in the setting of hig serum concentrations (>125 "g/ml), such as may occur with renal dysfunction (1,8). Besides gstrointestinal side effects, the manifestations of clinical toxicity include leukopenia and thrombocytopenia (1,8), which is similar to the toxicity associated with the anticancer drug 5-FU (2). Evidence that 5-FU might account for the clinical toxicity of 5-FC was suggested in previous studies in which catabolites of 5-FU were detected in the urine of patients being treated with 5-FC (9,11,16) and was most recently supported by the detection of elevated levels of 5-FU in 5-FC-treated patients who had developed myelosuppression (3).…”
mentioning
confidence: 98%
“…On the other hand, human cells could not convert 5-PC to 5-FU, and thus, there could be no interflerence of nucleic acid synthesis and thus no toxicity (9). However, toxicity does develop in patients treated with 5-FC and is seen most commonly in the setting of hig serum concentrations (>125 "g/ml), such as may occur with renal dysfunction (1,8). Besides gstrointestinal side effects, the manifestations of clinical toxicity include leukopenia and thrombocytopenia (1,8), which is similar to the toxicity associated with the anticancer drug 5-FU (2).…”
mentioning
confidence: 99%